2015
DOI: 10.1016/j.renene.2015.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion properties of a ternary nitrate/nitrite molten salt in concentrated solar technology

Abstract: a b s t r a c tThe enhancements in the storage systems developed by solar thermal power plants have provided to renewable energy a considerable increase in efficiency. Thermal Energy Storage (TES) using HITEC mixture could be used as Heat Transfer Fluid (HTF) in concentrated solar linear technology.In this research, the corrosive effects of HITEC mixture composed by 40 wt% NaNO 2 þ 7 wt % NaNO 3 þ 53 wt% KNO 3 were assessed at 390 C on a carbon steel (A516) and on low-Cr alloy steels (T11 and T22). The corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 18 publications
(12 reference statements)
0
19
0
3
Order By: Relevance
“…For example, Fernandez et al [8] have studied the corrosion effects of a ternary nitrate/nitrite molten salt mixture with piping/container alloys such as T22 steel, which showed a corrosion layer of 6.05 lm with a protective layer formed inside the material. The same group has also showed the improved physico-chemical properties of quaternary mixture of NaNO 3 , KNO 3 , LiNO 3 and Ca(NO 3 ) 2 compared to that of traditional 'Solar Salt' [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fernandez et al [8] have studied the corrosion effects of a ternary nitrate/nitrite molten salt mixture with piping/container alloys such as T22 steel, which showed a corrosion layer of 6.05 lm with a protective layer formed inside the material. The same group has also showed the improved physico-chemical properties of quaternary mixture of NaNO 3 , KNO 3 , LiNO 3 and Ca(NO 3 ) 2 compared to that of traditional 'Solar Salt' [9].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the nickel alloys with 15-20% chromium content showed best corrosion resistance, whereas iron alloys with low or almost zero nickel content exhibited poor corrosion resistance at high temperatures. Goods and Bradshaw [15] have reported a corrosion rate value of [6][7][8][9][10][11][12][13][14][15] lm per year at 570°C for two different stainless steels (SS-304 and SS-316) and 5 lm per year at 316°C for a carbon steel (A36), in contact with 'Solar Salt'. Using gravimetric immersion method, corrosion issues caused by Solar Salt at 390 and 550°C have been studied by Fernandez et al [16], on two different stainless steels (types AISI 304 and 430) and low-Cr ($2%) alloy steel (T22).…”
Section: Introductionmentioning
confidence: 99%
“…A great number of studies indicates that impurity levels tend to drive corrosion. The impurities of nitrates will have influence on the thermal behavior at elevated temperatures, put forward by Fernández et al . SO 4 2− and CO 3 2− easily form calcium, magnesium, sodium and potassium compounds, which can clog vessels, thus reducing the flow ability of the mixtures through the pipes of the solar centrals.…”
Section: Introductionmentioning
confidence: 96%
“…Diferentes estudios sobre la interacción entre el acero y las sales de nitrato se han desarrollado debido a que es necesario comprender los fenómenos que ocurren en la superficie del acero al estar en contacto con estos termofluidos. Todos estos trabajos han analizado los productos de corrosión por medio de SEM-EDS y DRX en la capa formada después de la exposición a las sales, demostrando la viabilidad del uso de distintos aceros para su posible implementación en plantas de concentración solar, además demostraron la eficiencia de las sales de nitrato para transportar la energía térmica [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introduccionunclassified